Teacher's Strategies in Developing 5-6 Years Old Kindergarteners' Fine Motor Skills: A Study in Pesisir Selatan, West Sumatra, Indonesia - Revormis, Revormis; Saridewi, Saridewi (GENIUS: Indonesian Journal of Early Childhood Education, 2022)
This study aims to describe the development of fine motor skills in a kindergarten in district of Pesisir Selatan, Province of West Sumatra, Indonesia, where the average age of the students is 5-6 years. By using a qualitative approach. The data collection that the researcher uses is observation, interviews, and documentation. This research showed that the teachers implemented the fine motor development strategies well. The teacher prepared plans, including compiling a semester program (PROSEM) in fine motor development. Teachers also always prepare the Daily Learning Plan Weekly Plan (RPPM) and Daily Learning Plan (RPPH) at the beginning of the school year. The method used by the teacher is also appropriate, and the media used is varied enough so that it can be interesting for kindergarten children to hone students abilities in developing fine motor skills.     Abstrak Penelitian ini bertujuan untuk mendeskripsikan bagaimana pengembangan keterampilan motorik halus di sebuah taman kanak-kanak di Kabupaten Pesisir Selatan, Provinsi Sumatera Barat, Indonesia, yang rata-rata berusia 5-6 tahun. Dengan menggunakan pendekatan kualitatif. Pengumpulan data yang peneliti gunakan adalah observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa strategi pengembangan motorik halus guru dilaksanakan dengan baik. Hal ini terlihat dari perencanaan yang disusun oleh guru, diantaranya dengan menyusun Program Semester (PROSEM) bidang pengembangan motorik halus. Guru juga selalu menyiapkan Rencana Pembelajaran Harian Rencana Mingguan (RPPM) dan Rencana Pembelajaran Harian (RPPH) di awal tahun ajaran. Metode yang digunakan guru juga sudah sesuai dan media yang digunakan cukup bervariasi sehingga dapat menarik minat anak-anak untuk mengasah kemampuan dalam mengembangkan motorik halusnya.